A perspective on situational judgment tests: From measures of situational judgment to measures of general domain knowledge. (July 2021) - Shaw, Amy
Abstract: Lievens and Motowidlo (2016) proposed to reconceptualize situational judgment tests (SJTs) as a category of measures assessing general knowledge about the utility of exhibiting workplace behaviors that represent either high or low levels of a targeted personality trait. However, the development of such contextual knowledge is unclear and less well addressed. Expanding this theoretical discussion, the present perspective explores the formation mechanisms of knowledge about interpersonal problem-solving within the Process-Personality-Interests-Knowledge (PPIK; Ackerman, 1996) framework of adult intellectual development. The current discussion highlights the roles of both cognitive and non-cognitive factors in the development of job knowledge, and that knowledge of workplace effective behaviors serves as a proximal determinant of performance relative to more distal predictors (e.g., personality) commonly used in personnel selection tests.